PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN AEROBIK ATLET SEKOLAH SEPAKBOLA PORSETA FC KECAMATAN LAREH SAGO HALABAN - Afdal Zikri; Apri Agus (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2018)
The research problem is still not good Aerobic endurance of Porseta Football School Athlete, Lareh Sago Halaban SubDistrict, 50 Kota District. This study aims to determine the effect of interval training on aerobic endurance of Porseta Football School Athlete, Lareh Sago Halaban SubDistrict 50 Kota District. This type of research is experimental research. the population in this study were all of the Porseta Football School players Lareh Sago Halaban SubDistrict 50 Kota District., totaling 20 people. The sampling technique was by purposive sampling technique, the sample was taken from under 19 year players, amounting to 15 people. Data collection was carried out by pre-test and post-test. Aerobic Endurance of Porseta Football School Athlete, Lareh Sago Halaban SubDistrict 50 Kota District, using the Yo-Yo Intermitten Endurance Test. Data analysis and hypothesis testing using comparative analysis techniques using the mean difference test formula (t test) with a significant level of α = 0.05. From the data analysis, the results were obtained: The effect of interval training on aerobic endurance of Porseta Football School Athlete, Lareh Sago Halaban SubDistrict 50 Kota District, with the acquisition of